Effect of orotic acid addition on hydrolysis conversion of α‐tricalcium phosphate to hydroxyapatite. Issue 6 (8th November 2021) - Yamada, Iori; Galindo, Tania Guadalupe Peñaflor; Noda, Daichi; Tagaya, Motohiro
Abstract: Alpha‐tricalcium phosphate (α‐TCP), which can be converted to calcium‐deficient hydroxyapatite (HA) by hydrolysis reaction, has been researched as a bone filling. Although the composites of α‐TCP with various organic molecules can exhibit a novel functionality, the reaction based on the addition of the interactive organic molecules has not been understood. Investigation of the hydrolysis conversion process under various conditions can lead to the elucidation of the biomineralization process. In this study, we investigated the hydrolysis conversion of α‐TCP to HA in the presence of orotic acid (Ort). As a result, the conversion rate from α‐TCP to HA at the reaction time of 3 h was improved to be more than five times as compared to that in the absence of Ort. Moreover, the addition of Ort promoted the crystal growth and suppressed the crystal growth in the m ‐plane direction. Furthermore, the mechanism for promoting HA formation is assumed to be related to the molecular structure of Ort, which is capable of forming the interactions between carboxylate and Ca 2+ ions.